(untitled) (Damascus University Journal for legal sciences, 2026)
Sexual crimes (rape, fornication, kidnapping with the intention of debauchery) committed on the female with her physical and psychological integrity, and constitute a flagrant attack on her public and sexual honor and freedom, but more than that, she finds herself forced to marry those who caused her all this under the pressure of tribal customs and traditions rooted in social structures, Most contemporary penal legislation has been affected by this, encouraging it on the pretext that it is the best solution for the victim, by rewarding the perpetrator of such crimes if he marries his victim with exemption from punishment, suspension of criminal proceedings against him or reduction of the prescribed sentence. This research came to find out the position of the Syrian legislator on the marriage of the perpetrator of sexual crimes (rape, fornication, kidnapping with the intention of debauchery) to his victim, and to evaluate his philosophy towards that and the extent to which it is consistent with international agreements and covenants on women’s rights, and with the requirements of contemporary penal policy